Evolving international monetary and financial architecture and the development challenge: A liquidity preference theoretical perspective - Jörg Bibow (Levy Economics Institute of Bard College, 2019)
This paper investigates the peculiar macroeconomic policy challenges faced by emerging economies in today's monetary (non)order and globalized finance. It reviews the evolution of the international monetary and financial architecture against the background of Keynes's original Bretton Woods vision, highlighting the US dollar's hegemonic status. Keynes's liquidity preference theory informs the analysis of the loss of policy space and widespread instabilities in emerging economies that are the consequence of financial hyperglobalization. While any benefits promised by mainstream promoters remain elusive, heightened vulnerabilities have emerged in the aftermath of the global crisis.
Keywords: B22; E43; E44; F02; F36; F65; G12; 330; Emerging Economies; Hyperglobalization; Liquidity; Liquidity PreferenceTheory; Reserve Accumulation; US Dollar Hegemony